A comprehensive investigation of protein expression profiles in L. monocytogenes exposed to thermal abuse, mild acid, and salt stress conditions - D'Onofrio, Federica; Schirone, Maria; Krasteva, Ivanka; Tittarelli, Manuela; Iannetti, Luigi; Pomilio, Francesco; Torresi, Marina; Paparella, Antonello; D'Alterio, Nicola; Luciani, Mirella (Frontiers in Microbiology, 2023)
Preventing L. monocytogenes infection is crucial for food safety, considering its widespread presence in the environment and its association with contaminated RTE foods. The pathogen’s ability to persist under adverse conditions, for example in food processing facilities, is linked to virulence and resistance mechanisms, including biofilm formation. In this study, the protein expression patterns of two L. monocytogenes 1/2a strains (268M and 3178-CB-2018), grown under environmental stressors (mild acidic pH, low temperature, and high concentration of NaCl), were investigated. Protein identification and prediction was performed by nLC-ESI-MS/MS and 9 different bioinformatic software, respectively. Gene enrichment analysis was carried out by STRING v11.05. A total of 1,215 proteins were identified, and of these 335 were non-cytosolic and 265 immunogenic proteins. Proteomic analysis revealed differences in protein expression between L. monocytogenes strains in stressing conditions. The two strains exhibited unique proteins expression profiles linked to stress response, virulence, and pathogenesis. Studying the proteomic profiles of such microorganism provides information about adaptation and potential treatments, highlighting its genetic diversity and demonstrating the utility of bioinformatics and proteomics for a broader analysis of pathogens.